Penerapan Metode Fisherface Untuk Mendeteksi Wajah Pada Citra Pasfoto - Wahyuni Safitri Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Face is one of the easiest physiological measures and is often used to distinguish individual identities from one another. Humans can distinguish faces from one person to another and remember someone's face quickly and easily. To read the characteristics of a face, a reader is needed, a database capable of storing facial pattern data and of course software that can analyze the data. Therefore, the method used in detecting faces is Fisherfaces, which is a new method of facial recognition. The advantage of using this method is that the processing time is relatively short / fast. This is because the fisherfaces process uses a process in the form of a matrix, making it suitable to be applied to systems that require real-time processing. But this method also has a drawback, namely that it requires a lot of templates so that the results of the introduction will be more accurate and optimal. Thus, achieving the maximum results from this research is certainly done with great effort. By using an online service, a web spreadsheet application on the www.think-maths.co.uk site that can convert digital images into pixels in the form of .xls format in the excel application